Effect of Deposition Temperature and Thermal Annealing on the Properties of Sputtered NiOx/Si Heterojunction Photodiodes - Roumen Nedev; David Mateos-Anzaldo; Eddue Osuna-Escalante; Oscar Perez-Landeros; Mario Curiel-Alvarez; Esteban Osorio-Urquizo; Jhonathan Castillo-Saenz; Javier Lopez-Medina; Benjamin Valdez-Salas; Nicola Nedev (Inorganics)
NiOx is a p-type semiconductor with excellent stability, which makes it interesting for a wide range of applications. Broadband photodetectors with high responsivity (R) were fabricated by depositing r.f.-sputtered NiOx layers on n-Si at room temperature (RT), 50 °C and 100 °C. In self-powered mode the RT diodes have R between 0.95 and 0.39 A/W for wavelengths between 365 and 635 nm, while at a reverse bias of −4 V, the responsivity increases to values between 22 A/W and 10.7 A/W for wavelengths in the same range. The increase of the deposition temperature leads to a decrease of R but also to a smaller reverse dark current. Thus, the 100 °C photodiodes might be more appropriate for applications where high responsivity is required, because of their smaller power consumption compared to the RT diodes. In addition, it was found that the increase of the deposition temperature leads to an increase of the diodes’ series resistance and the resistivity of NiOx. The effect of Rapid Thermal Annealing (RTA) on the properties of the photodiodes was studied. Annealing at 550 °C for 6 min leads to much higher responsivity compared to R of diodes with as-deposited NiOx. However, a disadvantage of the annealed diode is that the reverse current depends on the amplitude and polarity of previously applied bias voltage. The higher responsivity of the RTA photodiodes makes them useful as light sensors.